PROBLEMS OF ENVIRONMENT - Teshaboyeva Nafisa Zubaydulla qizi; Nishonova Munisa Oltinbek qizi (TADQIQOTLAR.UZ, 2024)
Annotation:This article highlights the various significant environmental problems facing the world today, including climate change, deforestation, pollution, loss of biodiversity, water scarcity, and resource depletion. The author discusses how human activities such as greenhouse gas emissions, deforestation, pollution, and over- exploitation of natural resources are contributing to these issues. The article emphasizes the importance of collective action at multiple levels to address these environmental challenges and promote sustainable development. It calls for efforts to reduce greenhouse gas emissions, conserve natural habitats, protect biodiversity, and ensure the sustainable use of resources to mitigate the impact on human health and ecosystems.